Analisis Pengaruh Indeks Pembangunan Manusia (IPM) dan Pertumbuhan Ekonomi Terhadap Kemiskinan di Kabupaten Pidie - Salbila Alfira Balqis; Puja Melati Sukma; Asnidar Asnidar; Nurlaila Hanum; Puti Andiny; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out whether HDI and economic growth have an effect on poverty in Pidie Regency, Aceh Province in the 2010-2023 period. The approach in this research is quantitative using multiple linear regression analysis methods. The Aceh Central Bureau of Statistics (BPS) data source uses Time Series data. . The results of this research show that HDI partially has a negative and significant effect on poverty in Pidie Regency, and Economic Growth has a positive and insignificant effect on partial poverty in Pidie Regency. And simultaneously HDI and Economic Growth have a positive and significant effect on poverty in Pidie Regency.